Thermal Analysis of Elliptic Bore Journal Bearing Considering the Effect of Shaft-Misalignment - Prakash Chandra Mishra (Japanese Society of Tribologists, 2011)
Bore ovality or non-circularity is due to manufacturing irregularity or running in. Misalignment is the non-parallel positioning of the shaft due to the nature of non-central dynamic loading, elastic deformation and thermal distortion of shaft. Misalignment may be also due to manufacturing error of shaft or bush. Study of combined effect of bore-out-of-roundness and shaft misalignment is important in bearing design. In this paper, the steady state characteristics of elliptic bore journal bearing are analyzed considering the shaft misalignment. A case specific film profile is derived to address the bore ellipticity together with shaft misalignment in eccentric positioning. Combined solution of Reynolds equation and Energy equation is carried out considering non-Newtonian piezo-viscous behavior of lubricant. The performance parameters such as film thickness, load carrying capacity, friction force, flow rate and side leakages are analyzed taking into account the thermal effect. The combined effect of bore non-circularity and shaft misalignment on temperature rise is also presented in this paper.